Clindamycin enhances opsonization of Staphylococcus aureus. - Milatovic, D (1983)
Staphylococcus aureus 502A was grown in the presence of one-third of the minimal inhibitory concentration of clindamycin. Phagocytosis of the antibiotic-treated bacteria by human polymorphonuclear leukocytes was significantly enhanced, compared with that of the untreated control (P less than 0.001). Study of opsonization kinetics by a chemiluminescence assay demonstrated that clindamycin-treated staphylococci were opsonized more rapidly than control bacteria and that the serum concentration required for sufficient opsonization was lower. Complement was consumed much faster, and the opsonic fragment C3b was fixed more rapidly to the bacterial surface when the staphylococci were preincubated with clindamycin. Electron micrographs showed an alteration of the staphylococcal cell wall after clindamycin treatment.